2001
DOI: 10.1021/ef0100698
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Produced from Charcoal Obtained by Vacuum Pyrolysis of Softwood Bark Residues

Abstract: Vacuum pyrolysis of softwood bark residues yields besides oil, charcoal as second valuable product. The activation behavior of the vacuum pyrolysis charcoal was compared to charcoal produced during conventional, atmospheric carbonization process. Steam activation of charcoal obtained by vacuum pyrolysis yields an activated carbon with a higher surface area than by using charcoal produced during atmospheric carbonization process. This can be related to the more open pore structure of the vacuum pyrolysis charco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This is far lower than the extents of char conversion (>55%) reported for the production of AC through physical activation with steam (BET surface areas > 800 m 2 / g). 53,54 Although the extent of char conversion in other DFB gasifiers might be >5%, the significantly lower fuel particle retention times in those gasifiers, as compared to those applied in the production of commercial AC, suggest that the extents of char conversion in those gasifiers could be lower than what is achieved during the production of commercial AC. Therefore, the BET surface area of the unconverted char that is circulated from the gasification chamber to the combustion chamber of a DFB gasifier will likely be lower than that of commercially produced AC.…”
Section: Introductionmentioning
confidence: 99%
“…This is far lower than the extents of char conversion (>55%) reported for the production of AC through physical activation with steam (BET surface areas > 800 m 2 / g). 53,54 Although the extent of char conversion in other DFB gasifiers might be >5%, the significantly lower fuel particle retention times in those gasifiers, as compared to those applied in the production of commercial AC, suggest that the extents of char conversion in those gasifiers could be lower than what is achieved during the production of commercial AC. Therefore, the BET surface area of the unconverted char that is circulated from the gasification chamber to the combustion chamber of a DFB gasifier will likely be lower than that of commercially produced AC.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-char is a pyrolytic by-product during bio-oil production [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. This oxygen-rich char is different from that formed by partial combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that vacuum pyrolysis derived char had a higher reactivity than atmospheric pyrolysis char due to a higher oxygen content of the vacuum pyrolysis char. Steam activation of charcoals obtained by vacuum and atmospheric pyrolysis of softwood bark residues was investigated by Cao et al [9,10]. Steam-activated carbons from charcoals, which were prepared by vacuum pyrolysis, yielded a higher surface area than those from charcoals produced from atmospheric carbonization.…”
Section: Introductionmentioning
confidence: 99%